A Recombinase Polymerase Amplification and Lateral Flow Strip Combined Method That Detects Salmonella enterica Serotype Typhimurium With No Worry of Primer-Dependent Artifacts - Wu, Huahua; Zhao, Panpan; Yang, Xiaohan; Li, Juan; Zhang, Jingyu; Zhang, Xun; Zeng, Zihan; Dong, Jingquan; Gao, Song; Lu, Chen (Frontiers in Microbiology, 2020)
On-site detection demands are quickly increasing to control foodborne pathogenic bacteria along with the long food supply chains. Combining the isothermal recombinase polymerase amplification (RPA) with lateral flow strips (LFS) is a promising molecular detection approach for the short reaction time, low isothermal condition, and simple and “instrument-free” procedure. However, the method comes with a non-negligible intrinsic risk of the primer-dependent artifacts. In this study, with an important foodborne pathogenic bacterium Salmonella enterica serotype Typhimurium (S. Typhimurium) as the model, system measures including the careful selection of primers targeting unique virulence genes, use of a probe in the RPA reaction, introducing base substitutions with specific guidelines in the primer and probe sequences, analyzing and screening the primer-probe complexes formation were taken to eliminate the primer-dependent artifacts. The measures were strictly tested for the efficacy, and the standardized method was able to specifically detect S. typhimurium within 30 min at 42oC without any interference of probe-primer signals. The established RPA-LFS method shared high sensitivity with the detection limit of 1 CFU/μL of unpurified culture. Our study provided practical measures for the prevention of false positive signals from primer-dimers or primer-probe complexes when using the RPA-LFS method in pathogen detections, and also established a readily applicable method for S. Typhimurium detection.